Exploring feminist public sphere through Henvalvani Community Radio: an empowerment through communication approach. Issue 3 (2nd October 2019) - Anand, Shweta; Kumar, Archna
Abstract : Identification of specific contributions made by community radio for translating the rhetoric of participation and empowerment into practice requires more attention. There is also a need to conduct more theoretical and empirical studies on "women and community radio." The study attempts to fulfill these needs to an extent, and offers a fresh perspective to look at the ways community radio can be evaluated. Women's narratives about the influence on health aspects by Henvalvani Community Radio situated in Chamba, a region of India, provided the necessary data and helped in finding the role of such participatory technologies in affecting the agency of the women. Habermas' Theory of Communicative Action and Kleine's Choice Framework guided the analysis. Empowerment through Communication (ETC) framework is proposed to provide a new perspective for comprehending the impact made by a community radio in influencing health seeking behavior of women. The study establishes Henvalvani Community Radio as a feminist public sphere helpful in altering the socio-cultural praxis of health communication.